Anisotropic and super-strong conductive hydrogels enabled by mechanical stretching combined with the Hofmeister effect. Issue 15 (7th March 2023) - Guo, Bingyan; Wu, Yukuan; He, Shaoshuai; Wang, Changyong; Yao, Mengmeng; Yu, Qingyu; Wu, Xiaojun; Yu, Chaojie; Liu, Min; Liang, Lei; Zhao, Zhongming; Qiu, Yuwei; et al.
Abstract : Anisotropic and super-strong conductive hydrogels were prepared by mechanical stretching combined with the Hofmeister effect. Anisotropic hydrogels exhibit anisotropic mechanical and electrochemical properties. Abstract : In the field of flexible electronic devices, conductive hydrogels have attracted great attention. However, it is difficult for existing hydrogel materials to realize excellent mechanical properties and high electrical conductivity simultaneously. To address this issue, this study proposes a facile method for producing super-strong conductive hydrogels via mechanical stretching combined with the Hofmeister effect. The anisotropic hydrogels possess highly anisotropic structures, which provide anisotropic mechanical properties and electrical conductivity. The prepared anisotropic hydrogels exhibit a combination of high strength (16.57 MPa), ultra-high toughness (39.23 MJ m −3 ), and high conductivity (0.38 S m −1 ), which are better than those of the anisotropic hydrogel along the vertical stretching direction and the isotropic hydrogel. And thus, the anisotropic hydrogels achieve a remarkable gauge factor (GF = 1.17). The anisotropic hydrogels demonstrate superior capabilities in human motion sensing. The excellent mechanical properties and high conductivity of anisotropic hydrogels make them a potential candidate for flexible electronic materials.